Sexualities, textualities, art and music in early modern Italy: playing with boundaries - Marshall, Melanie L.; McIver, Katherine A.; Carroll, Linda L.; McIver, Katherine A. (Ashgate, 2014)
Introduction. Playing with boundaries / Melanie L. Marshall, Linda L. Carroll, and Katherine A. McIver -- Performing sexuality. Visual pleasures, sensual sounds: music, morality, and sexuality in paintings by Titian / Katherine A. McIver -- Galeotto fu la metafora: language and sex in Boccaccio's Decameron / Catherine Baxter -- Balla la mona e salta il babuino: performing obscenity in a musical dialogue / Paul Schleuse -- The erotics of religion. Sexuality and depictions of the female saint in medieval Tuscany / Catherine Lawless -- Leonine lasciviousness and Luther / Anthony Cummings -- The Roman church and sexuality: some notes on prelates and regular clergy in sixteenth/seventeenth century Italian courts / Flavio Rurale -- Images of country life, realistic and artistic. Tradition and gender transgression: the iconography of the shepherd couple in Venetian pastoral landscape during the sixteenth century / Christophe Brouard -- (El) ge sa bon laorare: female wealth, male competition, musical festivities, and the Venetian patriciate in Ruzante's Pavan / Linda L. Carroll -- Farò quel che mi piacerà: fictional women in villotta voice resistance / Melanie L. Marshall